2017
DOI: 10.1186/s13068-017-0835-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined “de novo” and “ex novo” lipid fermentation in a mix-medium of corncob acid hydrolysate and soybean oil by Trichosporon dermatis

Abstract: BackgroundMicrobial oil is one important bio-product for its important function in energy, chemical, and food industry. Finding suitable substrates is one key issue for its industrial application. Both hydrophilic and hydrophobic substrates can be utilized by oleaginous microorganisms with two different bio-pathways (“de novo” lipid fermentation and “ex novo” lipid fermentation). To date, most of the research on lipid fermentation has focused mainly on only one fermentation pathway and little work was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The biomass, lipid concentration, and lipid content were determined as described by Wu [ 44 ]. The biomass was the cell dry weight per liter wastewater (g/L); the lipid concentration was the amount of lipid extracted from the cells per liter wastewater (g/L); and the lipid content was the mass percentage of lipid to biomass (% w/w) [ 45 ]. NH 4 + -N and TP were assayed with the Nessler’s reagent spectrophotometry method and ammonium molybdate spectrophotometric method, respectively [ 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…The biomass, lipid concentration, and lipid content were determined as described by Wu [ 44 ]. The biomass was the cell dry weight per liter wastewater (g/L); the lipid concentration was the amount of lipid extracted from the cells per liter wastewater (g/L); and the lipid content was the mass percentage of lipid to biomass (% w/w) [ 45 ]. NH 4 + -N and TP were assayed with the Nessler’s reagent spectrophotometry method and ammonium molybdate spectrophotometric method, respectively [ 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, to enhance the contact area between hydrophobic substrates and the cell surface, some external emulsifiers are often used to reduce the size of the hydrophobic substrates [42]. For example, in one study, oleaginous yeast Trichosporon dermatis CH007 was cultivated on a soybean oil-based medium along with Tween 80, Span 80, Tween 60, and OP-10 as external emulsifiers [43]. The addition of emulsifiers had a minor negative effect on the final lipid production.…”
Section: Resultsmentioning
confidence: 99%
“…The fatty acid profile of D5A differs from that of typical oleaginous yeasts. Whereas, in D5A, the fatty acids C16:0, C16:1n7, and C18:1n9 make up > 90% of the fatty acids, in general, in other oleaginous yeasts, e.g., Rhodotorula , Rhodosporidium , Yarrowia, Trichosporon , and Lipomyces species, the fatty acids C16:0 and C18:1n9 make up the bulk of the fatty acids with minor contributions from C16:1n7, C18:0, and C18:2n6 [ 5 , 6 , 8 , 11 , 39 ]. In general, the change in fatty acid composition of these two strains differed as the culture cells matured.…”
Section: Resultsmentioning
confidence: 99%
“…As current lipid productivities are not sufficient for producing lipid-based biofuels economically, a significant research to increase lipid accumulation or include the production of co-products to enable lipid-based biofuel production is ongoing [ 2 , 3 , 7 ]. Lipid accumulation in yeast can be through de novo biosynthesis, the fermentation of hydrophilic substrates such as sugars or other carbohydrates to lipids, or through ex novo biosynthesis, the conversion of hydrophobic substrates such as oil and alkanes [ 6 , 8 ]. Studies of oleaginous microorganisms, such as microalgae, yeasts, filamentous fungi, and bacteria, have revealed that de novo lipid metabolism is dependent on environmental conditions, particularly nutrient shortages with an excess of carbohydrates [ 1 , 9 11 ], while ex novo biosynthesis is not [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation